Analysis of Factors Related to Student Stress Levels During Online Learning at Muhammadiyah University East Kalimantan - Dwi Rahmah Fitriani; Mukhripah Damaiyanti; Rini Ernawati; Yulia Saputri; Zulliani Akbar; Utami Wahyu Lestari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Online learning needs to be a concern because it has positive and negative impacts, this can cause student stress due to various influencing factors. Procrastination is the tendency to postpone a task or job. Social support is something that needs attention and is associated with material and non-material support for students. Self-efficacy is the ability possessed by individuals to achieve certain desired results in carrying out an action or task. This study aimed to determine the relationship between procrastination, social support, and self-efficacy and student stress during online learning. The purpose of this study was to analyze the relationship between procastination factors, social support and self-efficacy with student stress levels during online learning. This study employed descriptive correlational design with crosssectional approach and examined 707 students of Muhammadiyah University East Kalimantan with a purposive sampling method. Procastination was measured using the APS (0.901), social support using the MSPSS ( 0.85), and self-efficacy using GSE ( 0.83). Stress was measured using DASS (0.755). The instrument used is the Indonesian language version which has been tested for validity and reliability. The results show that respondents had 247 (34.9%) high procrastination, 318 (45%) moderate social support, 364 (51.5%) high self-efficacy. Respondents experienced severe stress 261 (36.9%). The results of the gamma correlation test obtained a p value of 0.000 < (0.05) there is a significant relationship between procrastination, social support and self-efficacy with student stress levels during online learning. It is hoped that educational institutions and parents can play an active role in reducing other factors that cause stress during online learning.